2019
DOI: 10.1101/664987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity of fall armyworm, Spodoptera frugiperda and their gut bacterial community in Kenya

Abstract: 9The invasive fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) is a polyphagous pest that causes 10 widespread damage particularly to maize and sorghum in Africa. The microbiome associated with S. 11frugiperda could play a role in their success and adaptability. However, these bacterial communities remain 12 poorly studied, especially for S. frugiperda in Africa. We investigated the composition, abundance and 13 diversity of microbiomes associated with larval and adult specimens of S. frugiperda collect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 88 publications
2
14
0
Order By: Relevance
“…These findings are in agreement with the recent report by Gichuhi et al. (2020) on the occurrence of the same bacteria groups in S. frugipeda in their study.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings are in agreement with the recent report by Gichuhi et al. (2020) on the occurrence of the same bacteria groups in S. frugipeda in their study.…”
Section: Discussionsupporting
confidence: 94%
“…Four bacteria genera, Enterococcus , Pseudomonas , Delftia and Serratia , observed in this study have previously been isolated from S. frugiperda (Almeida, Moraes, Trigo, Omoto, & Cônsoli, 2017); Acevedo et al, 2017; Gichuhi et al., 2020). Additionally, Staphylococcus , Microbacterium and Arthrobacter recorded were previously isolated from S. frugiperda in Brazil (Almeida et al., 2017).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Bacteria of those two phyla accounted for more than 98% of the total intestinal bacteria of the three grasshopper species, which was consistent with previous reports on the primary species of insect microbiomes. Previous studies have shown that Proteobacteria are the primary bacteria in the intestinal tract of many insects: Schistocerca gregaria in Orthoptera (Dillon et al, 2010), Acyrthosiphon pisum in Hemiptera, and Ectropis obliqua (Engel & Moran, 2013) and Spodoptera frugiperda (Gichuhi et al, 2020) in Lepidoptera. Among the Lepidoptera insects studied, the primary bacteria in the intestinal tract of Lymantria dispar, Helicoverpa armigera, Bombyx mori and Plutella xylostella larvae are Proteobacteria and Firmicutes (Zhou et al, 2015;Priya et al, 2012;Broderick et al, 2004).…”
Section: Discussionmentioning
confidence: 99%